Causes of death and renal tubular dysfunction in residents exposed to cadmium in the environment. Issue 8 (6th April 2006) - Nishijo, M; Morikawa, Y; Nakagawa, H; Tawara, K; Miura, K; Kido, T; Ikawa, A; Kobayashi, E; Nogawa, K
Abstract : Objectives: To clarify the causes of death of residents with renal tubular dysfunction induced by cadmium (Cd) in the environment. Methods: A 15 year follow up study was performed with the inhabitants living in the Cd polluted Kakehashi River basin in Japan. Standardised mortality ratios (SMRs) for causes of death, classified by ICD-9, were computed using the person-years method to investigate the excess mortality of subjects with urinary β2-MG (microglobulin) ⩾1000 μg/gCr. Mortality risk analysis was performed using Cox's proportional model to compare mortality between subjects with urinary β2-MG ⩾1000 and <1000 μg/gCr, and to investigate the relationship between the degree of urinary β2-MG and mortality. Results: Excess mortality due to heart failure and cerebral infarction in both sexes, and nephritis and nephrosis in men, was observed among subjects with urinary β2-MG ⩾1000 μg/gCr. Significant increases in mortality risk for cerebral infarction in men and for malignant neoplasms in women with urinary β2-MG ⩾1000 μg/gCr were observed during the first five year observation period. For nephritis and nephrosis, the mortality risks for men and women with urinary β2-MG ⩾1000 μg/gCr significantly increased over the 15 year observation period. The mortality risks for heart failure and cerebral infarction increased in proportion to the increased urinary β2-MG in both sexes. Increased mortality risks for nephritis and nephrosis were identified in the subjects with urinary β2-MG ⩾10000 μg/gCr in both sexes. Conclusion: Renal tubular dysfunction induced by Cd affected the causes of death, and mortality for heart failure, cerebral infarction, and nephritis and nephrosis was increased among inhabitants living in a Cd polluted area in Japan. In women, cancer mortality may have been increased while Cd pollution was ongoing.